Early diagnosis of ataxia telangiectasia in the neonatal phase: a parents’ perspective - Schoenaker, M. H. D. (Eur J Pediatr, 2019)
Ataxia telangiectasia (A-T) is a severe neurodegenerative disorder with variable immunodeficiency. Together with the Dutch A-T community, we investigated the opinion of A-T parents on an early A-T diagnosis in the asymptomatic phase of the disease. During an annual national meeting for A-T patients and families, the topic of an early A-T diagnosis was discussed in relation to the recent introduction of neonatal screening for severe combined immunodeficiency (SCID) in the Netherlands. Based on the discussion, individual arguments were identified and processed into a questionnaire, which was sent out to 64 A-T parents (32 families). Arguments included were insecurity to diagnosis, possible medical advantages, appropriate genetic counseling and family planning, loss of “golden” year(s), and early cancer screening for parents. The response rate was 55% (n = 35 parents). Twenty-six (74%) parents felt that the advantages of an early diagnosis outweighed the disadvantages, five parents thought that the disadvantages would outweigh the advantages (14%), and four parents did not indicate a preference. Conclusion: The majority of parents of a child with A-T would have preferred an early diagnosis during the asymptomatic phase of the disease, because the uncertainty during the diagnostic process had had a major impact on their lives. In addition, the knowledge of being carriers of an ATM gene mutation influenced decisions about family planning. Parents who opposed against an early diagnosis emphasized the joy of having a seemingly healthy child until diagnosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00431-019-03479-5) contains supplementary material, which is available to authorized users.